Label-Free Impedimetric Immunosensors Modulated by Protein A/Bovine Serum Albumin Layer for Ultrasensitive Detection of Salbutamol - Lin, Chia-Hung (Sensors (Basel), 2020)
The sensing properties of immunosensors are determined not only by the amount of immobilized antibodies but also by the number of effective antigen-binding sites of the immobilized antibody. Protein A (PA) exhibits a high degree of affinity with the Fc part of IgG antibody to feasibly produce oriented antibody immobilization. This work proposes a simple method to control the PA surface density on gold nanostructure (AuNS)-deposited screen-printed carbon electrodes (SPCEs) by mixing concentration-varied PA and bovine serum albumin (BSA), and to explore the effect of PA density on the affinity attachment of anti-salbutamol (SAL) antibodies by electrochemical impedance spectroscopy. A concentration of 100 μg/mL PA and 100 μg/mL BSA can obtain a saturated coverage on the 3-mercaptoproponic acid (MPA)/AuNS/SPCEs and exhibit a 50% PA density to adsorb the amount of anti-SAL, more than other concentration-varied PA/BSA-modified electrodes. Compared with the randomly immobilized anti-SAL/MPA/AuNS/SPCEs and the anti-SAL/PA(100 μg/mL):BSA(0 μg/mL)/MPA/AuNS/SPCE, the anti-SAL/PA(100 μg/mL): BSA(100 μg/mL)/MPA/AuNS/SPCE-based immunosensors have better sensing properties for SAL detection, with an extremely low detection limit of 0.2 fg/mL and high reproducibility (<2.5% relative standard deviation). The mixture of PA(100 μg/mL):BSA(100 μg/mL) for the modification of AuNS/SPCEs has great promise for forming an optimal protein layer for the oriented adsorption of IgG antibodies to construct ultrasensitive SAL immunosensors.